A full-spectrum light-absorbing MoS2 phase-doped material, its preparation method and application

CN120396498BActive Publication Date: 2026-10-30WUHAN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510595866.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-09
Publication Date
2026-10-30
Estimated Expiration
2045-05-09

AI Technical Summary

Technical Problem

现将2H相MoS2转化为1T相的方法主要包括锂离子嵌入、高温退火、电子束扫描和表面掺杂等,但1T相MoS2仍存在的热稳定性和化学稳定性差的问题,影响实际应用

Benefits of technology

1、本发明的全光谱吸光MoS2相掺杂材料的制备方法,通过电化学辅助超声法从辉钼矿薄片中剥离含S空位的少层MoS2,再对制备的MoS2进行高温退火处理,使其基面上的S空位结构形成1T@2H相掺杂阵列,增强了材料在全光谱尤其是近红外区的光吸收能力。避免了传统复合材料在制备过程中存在的合成复杂、效率低、产生副产物等问题,缩减成本,提高了材料的资源利用效率。全光谱吸光MoS2相掺杂材料在使用10个循环后仍保持非常稳定的蒸发速率,蒸发速率从1.27 kg·m-2·h-1变为1.26 kg·m-2·h-1;本发明通过对MoS2进行原位相掺杂,显著提升了MoS2相掺杂材料的光热性能,具体体现在以下:通过电化学辅助超声法,成功从辉钼矿薄片中剥离含S空位的少层MoS2纳米片。通过高温退火处理,使其基面上的S空位结构形成1T@2H相掺杂阵列,拓宽了材料在全光谱上的吸光范围,尤其是近红外区(1000-2500 nm)光吸收能力提升近71%,从而实现全光谱吸光的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120396498B_ABST
    Figure CN120396498B_ABST
Patent Text Reader

Abstract

The application provides a full-spectrum light-absorbing MoS2 phase-doped material and a preparation method and application thereof. The application peels off a few-layer MoS2 containing S vacancies from molybdenite flakes through an electrochemical-assisted ultrasonic method, and then performs high-temperature annealing treatment on the MoS2, so that the S vacancy structure on the basal plane of the MoS2 forms a 1T@2H phase-doped array, and the light absorption capacity of the material in the full spectrum, especially in the near-infrared region, is enhanced. The application expands the volume of the molybdenite to 20 times of the original volume by regulating the electrolysis time and voltage. By controlling the temperature and time of the heat treatment, in-situ phase doping of the MoS2 is realized, and the localized surface plasmon resonance (LSPR) effect of the 1T phase MoS2 and the electron-hole non-radiative relaxation process of the 2H phase MoS2 are coordinated, so that the light absorption spectrum of the material is widened, and excellent photothermal performance is also exhibited, especially the light absorption capacity in the near-infrared region is increased by nearly 71%, thereby realizing the effect of full-spectrum light absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photothermal conversion materials technology, and in particular to a full-spectrum light-absorbing MoS2 phase doped material, its preparation method, and its application. Background Technology

[0002] With the increasing scarcity of freshwater resources, solar-driven interfacial evaporation technology has garnered widespread attention due to its sustainability. Traditional seawater desalination methods are limited by high energy consumption and negative environmental impacts, while interfacial solar seawater desalination technology, relying on abundant renewable energy sources, has become a promising alternative. The performance of the photothermal conversion materials directly determines the overall efficiency of the solar evaporation system.

[0003] Molybdenum disulfide (MoS2) has become a focus of research due to its unique two-dimensional structure and excellent photothermal properties. However, because MoS2's intrinsic band gap is only 1.8–1.9 eV, it can only absorb sunlight in the 200–700 nm wavelength range, failing to effectively absorb photons in the near-infrared region (which accounts for 53% of the full spectrum), thus limiting its overall photothermal conversion efficiency. Therefore, improving the light absorption capacity of MoS2 in the near-infrared region is key to enhancing its performance.

[0004] Currently, common methods to improve the photothermal conversion performance of MoS2 involve combining it with other materials, such as noble metals, semiconductors, or organic polymers, utilizing localized surface plasmon resonance (LSPR), near-zero bandgap semiconductor properties, and conjugation effects to enhance near-infrared absorption. However, these methods typically suffer from complex synthesis processes, high costs, and low efficiency, and may generate byproducts, reducing the material's resource utilization efficiency. MoS2 exists in different crystal phases, including the metallic 1T phase and the semiconductor 2H phase. Among them, the 1T phase MoS2 can generate the localized surface plasmon resonance (LSPR) effect, effectively capturing photons in the near-infrared region and improving photothermal conversion efficiency. Current methods for converting 2H phase MoS2 to the 1T phase mainly include lithium-ion intercalation, high-temperature annealing, electron beam scanning, and surface doping, but the poor thermal and chemical stability of the 1T phase MoS2 still affects practical applications.

[0005] Given the current shortcomings in the preparation of MoS2 phase doped materials, it is necessary to improve upon them. Summary of the Invention

[0006] In view of this, the present invention provides a full-spectrum light-absorbing MoS2 phase doped material, its preparation method and application, to overcome the defects existing in the prior art.

[0007] In a first aspect, the present invention provides a method for preparing a full-spectrum light-absorbing MoS2 phase-doped material, comprising the following steps: MoS2 nanosheets containing S vacancies were obtained by electrolytic expansion and ultrasonic exfoliation of molybdenite sheets. Annealing of MoS2 nanosheets containing S vacancies yields 1T@2H MoS2 phase-doped materials with full-spectrum absorption. Spandex fabric is prepared by immersing it in water-based polyurethane to obtain a hydrophilic modified spandex fabric. A substrate is bonded to a modified spandex fabric, and then a spandex fabric is bonded to the surface of the modified spandex fabric. The 1T@2H MoS2 phase doped material was mixed with ethanol, coated onto the surface of spandex cloth, dried, and then coated with polytetrafluoroethylene emulsion and dried to obtain a full-spectrum light-absorbing MoS2 phase doped material.

[0008] Preferably, the method involves electrolytically expanding and ultrasonically exfoliating molybdenite sheets to obtain MoS2 nanosheets containing S vacancies, specifically including the following steps: Using molybdenite sheets as cathodes, electrolysis is performed by placing the cathode and anode in an electrolyte and connecting them to a power source to obtain expanded molybdenite sheets. Expanded molybdenite sheets were used as anodes for continuous electrolysis to obtain molybdenite sheets containing S vacancies. Molybdenite flakes containing S vacancies were immersed in NMP and ground to obtain a pre-exfoliated product. The pre-exfoliated product was sonicated, centrifuged, filtered, and freeze-dried to obtain MoS2 nanosheets containing S vacancies. In this method, molybdenite sheets are used as cathodes, and electrolysis is performed by placing the cathode and anode in an electrolyte and connecting them to a power source. Alternatively, expanded molybdenite sheets are used as anodes for continuous electrolysis. The controlled process parameters for electrolysis are: 0.5–0.8 mol / L NaOH solution as the electrolyte, and a current density of 0.02–0.03 A / cm². 2 The electrolysis time is 10~12h.

[0009] Preferably, in the step of sonicating, centrifuging, filtering, and freeze-drying the pre-exfoliated product to obtain MoS2 nanosheets containing S vacancies, the sonication power is 400~500 W, the sonication time is 4~6 h, the centrifugation rate is ~6000 rpm, and the centrifugation time is 20~30 min.

[0010] Preferably, in the step of annealing the MoS2 nanosheets containing S vacancies, the annealing temperature is 200~360℃ and the time is 12~24h.

[0011] Preferably, in the step of immersing the spandex in water-based polyurethane, the immersion time is 0.5 to 1 hour.

[0012] Preferably, in the step of mixing the 1T@2H MoS2 phase doped material and ethanol, the mass-to-volume ratio of the 1T@2H MoS2 phase doped material and ethanol is (20~40) mg:(6~10) mL.

[0013] Preferably, the substrate is a polylactic acid substrate, and the substrate is a hemispherical substrate.

[0014] Secondly, the present invention also provides a full-spectrum light-absorbing MoS2 phase doped material, which is prepared by the aforementioned preparation method.

[0015] Thirdly, the present invention also provides a full-spectrum light-absorbing MoS2 phase doped material prepared by the preparation method described above, or the full-spectrum light-absorbing MoS2 phase doped material described above, as a solar-driven interfacial evaporation material for seawater desalination or high-salt wastewater treatment.

[0016] The present invention has the following advantages over the prior art: 1. The method for preparing full-spectrum light-absorbing MoS2 phase-doped materials of the present invention involves exfoliating few-layer MoS2 containing S vacancies from molybdenite flakes using an electrochemical-assisted ultrasonic method, followed by high-temperature annealing of the prepared MoS2 to form a 1T@2H phase-doped array of S vacancies on the basal surface, thereby enhancing the material's light absorption capacity across the entire spectrum, especially in the near-infrared region. This method avoids the problems of complex synthesis, low efficiency, and by-product generation in the preparation of traditional composite materials, reducing costs and improving the resource utilization efficiency of the material. The full-spectrum light-absorbing MoS2 phase-doped material maintains a very stable evaporation rate after 10 cycles of use, with the evaporation rate decreasing from 1.27 kg·m³. -2 ·h -1 It becomes 1.26 kg·m -2 ·h -1 This invention significantly improves the photothermal properties of MoS2 phase-doped materials through in-situ phase doping, specifically as follows: Few-layer MoS2 nanosheets containing S vacancies were successfully exfoliated from molybdenite flakes using an electrochemical-assisted ultrasonic method. High-temperature annealing then formed a 1T@2H phase-doped array of S vacancies on the basal surface, broadening the material's absorption range across the entire spectrum, particularly increasing the near-infrared (1000-2500 nm) light absorption capacity by nearly 71%, thus achieving full-spectrum absorption.

[0017] 2. The full-spectrum light-absorbing MoS2 phase-doped material prepared by this invention exhibits excellent economic benefits and performance, with an evaporation rate of 0.991 kg·m⁻² compared to the original MoS2 nanosheets. -2 ·h -1 The photothermal conversion efficiency was 74.21%. The evaporation rate of the full-spectrum light-absorbing MoS2 phase-doped material was 1.27 kg·m³.-2 ·h -1 The photothermal conversion efficiency is 90.52%. The full-spectrum light-absorbing two-dimensional molybdenite composite material maintains a very stable evaporation rate after 10 cycles, with an evaporation rate of 1.26 kg·m³ after 10 cycles. -2 ·h -1 The treated seawater contains Na + Mg 2+ K + and Ca 2+ The concentrations of major ions are significantly reduced, by at least three orders of magnitude, meeting WHO drinking water standards. The full-spectrum light-absorbing MoS2 phase-doped material exhibits a uniform surface temperature distribution and concentrated central heat, demonstrating rapid response during photothermal conversion. This invention's full-spectrum light-absorbing molybdenum disulfide phase-doped material possesses excellent water purification performance, stability, and thermal management capabilities, making it suitable for practical solar desalination applications. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 This is a structural diagram of the full-spectrum light-absorbing MoS2 phase doped material prepared in Example 1; Figure 2 Schematic diagrams of photothermal evaporation devices of different shapes assembled from light-absorbing MoS2 phase doped materials prepared on substrates of different shapes in Examples 1 and 7-8; Figure 3 The images show the water contact angle test results of the modified spandex fabric and the spandex fabric coated with polytetrafluoroethylene in Example 1. Figure 4 Comparison of photothermal evaporation performance of light-absorbing MoS2 phase doped materials prepared on substrates of different shapes in Examples 1 and 7-8; Figure 5 The images show SEM images of the spandex fabric in Example 1 before and after loading with MoS2 phase doped material. Figure 6 The image shows the FTEM image of the 1T@2H MoS2 phase doped material prepared in step S2 of Example 1. Figure 7 The images show the XRD patterns of 1T@2H MoS2 phase doped materials prepared under different conditions in step S2 of Examples 1-3 and the MoS2 nanosheets in step S1. Figure 8XPS image of the 1T@2H MoS2 phase doped material prepared in step S2 of Example 1; Figure 9 The images show the UV-Vis-NIR spectra of 1T@2H MoS2 phase doped materials prepared under different conditions in steps S2 of Examples 1, 2, 4-6. Figure 10 The graph shows the change in mass loss of Bohai Sea water over time during the evaporation experiment of the full-spectrum light-absorbing MoS2 phase doped materials in Examples 1-3. Figure 11 The evaporation rate and photothermal conversion efficiency of the full-spectrum light-absorbing MoS2 phase doped materials in Examples 1-3 were calculated after an evaporation experiment lasted 1 h. Figure 12 The graph shows the changes in various ions in the full-spectrum light-absorbing MoS2 phase doped material prepared in Example 1 before and after evaporation from Bohai Sea water. Figure 13 The evaporation rate of the full-spectrum light-absorbing MoS2 phase doped material prepared in Example 1 during the evaporation of Bohai Sea water over 10 desalination cycles is shown in the graph. Detailed Implementation

[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of embodiments. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a rigid limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single digits within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Additionally, whenever a numerical range is indicated herein, it means including any referenced number (fraction or integer) within the indicated range.

[0022] This application provides a method for preparing a full-spectrum light-absorbing MoS2 phase-doped material, comprising the following steps: S1. MoS2 nanosheets containing S vacancies were obtained by electrolytic expansion and ultrasonic exfoliation of molybdenite sheets. S2. Annealing MoS2 nanosheets containing S vacancies yields 1T@2H MoS2 phase-doped material with full-spectrum light absorption. S3. Immerse the spandex in water-based polyurethane to obtain a hydrophilic modified spandex fabric. S4. A base is bonded to a modified spandex fabric, and then a spandex fabric is bonded to the surface of the modified spandex fabric. S2. Mix 1T@2H MoS2 phase doped material with ethanol, coat it onto the surface of spandex cloth, dry it, then coat it with polytetrafluoroethylene emulsion and dry it to obtain full-spectrum light-absorbing MoS2 phase doped material.

[0023] In some embodiments, MoS2 nanosheets containing S vacancies are obtained from molybdenite using an electrochemical-assisted liquid-phase exfoliation method, specifically including the following steps: S11. Using molybdenite sheets as cathodes, electrolyze the cathodes and anodes in an electrolyte and connect them to a power source to obtain expanded molybdenite sheets. S12. Reverse the electrode connection and use the expanded molybdenite sheet as the anode for continuous electrolysis to obtain a molybdenite sheet containing S vacancies. S13. Molybdenite flakes containing S vacancies are immersed in NMP (i.e., N-methylpyrrolidone) and ground to obtain a pre-exfoliated product. S14. The pre-exfoliated product was sonicated, centrifuged, filtered, and freeze-dried to obtain MoS2 nanosheets containing S vacancies. In this method, molybdenite sheets are used as cathodes, and electrolysis is performed by placing the cathode and anode in an electrolyte and connecting them to a power source. Alternatively, expanded molybdenite sheets are used as anodes for continuous electrolysis. The controlled process parameters for electrolysis are: 0.5–0.8 mol / L NaOH solution as the electrolyte, and a current density of 0.02–0.03 A / cm². 2 The electrolysis time is 10~12h.

[0024] Specifically, using molybdenite sheets as cathodes, the cathode and anode are placed in an electrolyte, and the cathode and anode are connected to the negative and positive terminals of a power supply, respectively. Electrolysis is performed by controlling the current, and the molybdenite sheets expand after electrolysis, resulting in expanded molybdenite sheets. Then, the electrodes are reversed, and the expanded molybdenite sheets are used as anodes connected to the positive terminal of the power supply. Electrolysis is performed by controlling the current, resulting in molybdenite sheets containing S vacancies. Specifically, the material containing S vacancies is a MoS2 nanosheet in which some sulfur (S) atoms are missing, forming vacancies. This structural defect greatly changes the electronic structure and chemical properties of the material. On the one hand, S vacancies act as active sites, significantly enhancing the chemical reactivity of the material. On the other hand, S vacancies also affect the electrical properties of the material, changing its conductivity and carrier concentration. 1T@2H MoS2 phase-doped materials refer to the doping of MoS2 with 1T and 2H phases having different crystal structures. The 2H phase is a common semiconductor phase of MoS2, with good stability but limited electrical properties; the 1T phase is a metallic phase with excellent electrical properties, abundant active sites, and high charge transfer efficiency, but poor stability. By doping the 1T phase into the 2H phase to form 1T@2H MoS2, the advantages of both can be combined, enabling the material to maintain a certain level of stability while possessing better electrical and catalytic properties. Introducing S vacancies can sometimes promote the formation and stabilization of the 1T phase in the 2H phase, which helps to achieve more effective phase doping; conversely, the 1T@2H phase doping structure may also affect the properties and distribution of S vacancies, and the synergistic effect of the two further optimizes the material properties.

[0025] This invention employs an electrochemical-assisted ultrasonic method to exfoliate few-layer MoS2 containing S vacancies from molybdenite thin sheets. The prepared MoS2 is then subjected to high-temperature annealing, causing the S vacancy structure on its basal surface to form a 1T@2H phase-doped array. This enhances the material's light absorption capacity across the entire spectrum, especially in the near-infrared region. This avoids the problems of complex synthesis, low efficiency, and byproduct generation inherent in traditional composite material preparation processes, reducing costs and improving resource utilization efficiency. Furthermore, by controlling the electrolysis time and voltage, the volume of molybdenite expands to 20 times its original size. By controlling the temperature and time of the heat treatment, in-situ phase doping of MoS2 is achieved, synergistically combining the localized surface plasmon resonance (LSPR) effect of the 1T phase MoS2 with the electron-hole nonradiative relaxation process of the 2H phase MoS2. This broadens the material's absorption spectrum while exhibiting excellent photothermal properties, particularly increasing light absorption capacity in the near-infrared region by nearly 71%, thus achieving full-spectrum light absorption. The full-spectrum light-absorbing molybdenum disulfide phase-doped material of the present invention has excellent water purification performance, stability and thermal management capabilities, and is suitable for practical solar desalination applications.

[0026] In some embodiments, in the step of sonicating, centrifuging, filtering, and freeze-drying the pre-exfoliated product to obtain MoS2 nanosheets containing S vacancies, the ultrasonic power is 400~500 W, the ultrasonic time is 4~6 h, the centrifugation rate is ~6000 rpm, and the centrifugation time is 20~30 min.

[0027] In some embodiments, the length and width of the molybdenite sheet are both 1~2 cm, and the thickness is 1~2 mm.

[0028] In some embodiments, MoS2 nanosheets containing S vacancies are placed in a tube furnace, and different temperatures and heat treatment times are set. After heating, the nanosheets are allowed to cool naturally to room temperature to obtain 1T@2H MoS2 phase-doped materials.

[0029] In some embodiments, in the step of annealing MoS2 nanosheets containing S vacancies in a tube furnace, the annealing temperature is 200~360℃ and the time is 12~24h.

[0030] Specifically, during the high-temperature annealing process, atoms around the sulfur vacancy regions undergo thermal motion and migration, causing a phase transition in the local structure of MoS2 and forming a 1T@2H phase-doped array. The local introduction of the 1T phase not only alters the band structure of MoS2 and introduces metallicity, but also enhances the local surface plasmon resonance (LSPR) effect, enabling it to more effectively absorb and utilize photons in the near-infrared region.

[0031] In some embodiments, in the step of immersing spandex in water-based polyurethane, the immersion time is 0.5 to 1 hour, and the mixture is stirred continuously during the immersion process.

[0032] In some embodiments, in the step of mixing 1T@2H MoS2 phase doped material and ethanol, the mass-to-volume ratio of 1T@2H MoS2 phase doped material and ethanol is (20~40) mg:(6~10) mL.

[0033] In some embodiments, the substrate is a polylactic acid substrate, and the substrate is a hemispherical substrate.

[0034] In some embodiments, a hemisphere is 3D printed using polylactic acid as the raw material as the base. Modified spandex fabric is then bonded to the surface of the model, and another layer of spandex fabric is bonded on the outside. 1T@2H MoS2 phase doping material and ethanol are mixed and uniformly coated onto the outermost spandex fabric. After natural drying, a layer of polytetrafluoroethylene emulsion is coated on the outside. After curing at room temperature, a full-spectrum light-absorbing MoS2 phase doping material is obtained.

[0035] This invention discloses a method for preparing full-spectrum light-absorbing MoS2 phase-doped materials. By creating a certain number of S vacancies on the MoS2 basal surface and optimizing the high-temperature annealing heat treatment conditions, a localized phase transition in MoS2 is achieved, significantly improving its light absorption performance and photothermal conversion efficiency. This method is particularly suitable for solar-driven interfacial evaporation, seawater desalination, wastewater treatment, and solar thermal power generation. The core innovation of this invention lies in the introduction of a 1T@2H phase doping array, which synergistically combines the localized surface plasmon resonance (LSPR) effect of the 1T phase MoS2 with the electron-hole nonradiative relaxation process of the 2H phase MoS2. This broadens the material's light absorption spectrum while exhibiting excellent photothermal performance, effectively enhancing the material's light-harvesting ability in the near-infrared spectral region by nearly 71%. In-situ phase doping avoids the problems of complex synthesis, low efficiency, and by-product generation in the preparation of composite materials, reducing costs and improving the resource utilization efficiency of the material. This invention provides a new strategy for low-cost, high-efficiency solar interfacial evaporation technology.

[0036] Based on the same inventive concept, the present invention also provides a full-spectrum light-absorbing MoS2 phase doped material, which is prepared by the preparation method described above.

[0037] Based on the same inventive concept, the present invention also provides a full-spectrum light-absorbing MoS2 phase doped material prepared by the above-mentioned preparation method, or the above-mentioned full-spectrum light-absorbing MoS2 phase doped material, as a solar-driven interfacial evaporation material for seawater desalination or high-salt wastewater treatment.

[0038] The following specific embodiments further illustrate the full-spectrum absorbance MoS2 phase doped material of this application, its preparation method, and its application. This section further illustrates the content of the present invention with reference to specific embodiments, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in the art.

[0039] The following examples use aqueous polyurethane emulsions purchased from Maclean's reagents, specifically: W909579 aqueous polyurethane, solid content: 60%; and polytetrafluoroethylene emulsions purchased from Maclean's reagents, specifically P816262 polytetrafluoroethylene concentrated dispersion, 60 wt% dispersion.

[0040] Example 1 This application provides a method for preparing a full-spectrum light-absorbing MoS2 phase-doped material, including the following steps: S1. Using a molybdenite sheet (1 cm in length and width, and 1 mm in thickness) as the cathode, the cathode and anode (graphite) are placed in an electrolyte (0.6 mol / L NaOH solution (aqueous solution)) and connected to a power source for electrolysis to obtain an expanded molybdenite sheet; the electrodes are reversed, and the molybdenite sheet is used as the anode for continuous electrolysis to obtain a molybdenite sheet containing S vacancies; In this process, the cathode and anode (the anode is graphite) are placed in the electrolyte and connected to a power source for electrolysis to obtain expanded molybdenite flakes. The controlled process parameters are: voltage of 7 V and electrolysis time of 10 h. When the electrodes are reversed, the molybdenite flakes are used as the anode for continuous electrolysis. The controlled process parameters are: voltage of 7 V and electrolysis time of 5 h. Molybdenite sheets containing S vacancies were soaked in NMP for 2 h, ground, sonicated at 500 W for 5 h, centrifuged at 6000 rpm for 20 min, filtered, and freeze-dried to obtain MoS2 nanosheets containing S vacancies. S2. Place the MoS2 nanosheets containing S vacancies in a tube furnace and anneal them at 260°C for 24 h. After they are naturally cooled to room temperature, 1T@2H MoS2 phase doped material is obtained. S3. Soak the spandex fabric in an aqueous polyurethane emulsion for 1 hour, stirring constantly to improve its hydrophilicity, and obtain a hydrophilic modified spandex fabric. S4. Use polylactic acid as raw material to 3D print a hemisphere (3cm radius) as the base. The modified spandex fabric is bonded to the substrate surface, and then another layer of spandex fabric is bonded to the surface of the modified spandex fabric. 30 mg of 1T@2H MoS2 phase doped material and 10 mL of ethanol were mixed and uniformly coated onto the outermost spandex cloth. After natural drying, a 2 mL layer of polytetrafluoroethylene emulsion was coated on the outside. After curing at room temperature, a photothermal evaporator for interfacial solar desalination was obtained, which is a full-spectrum light-absorbing MoS2 phase doped material.

[0041] Example 2 This embodiment provides a method for preparing a full-spectrum light-absorbing MoS2 phase doped material, which is the same as in Embodiment 1, except that in step S2, the MoS2 nanosheets containing S vacancies are placed in a tube furnace and annealed at 260°C for 12 h, and then allowed to cool naturally to room temperature to obtain 1T@2H MoS2 phase doped material. All other process parameters are the same as in Embodiment 1.

[0042] Example 3 This embodiment provides a method for preparing a full-spectrum light-absorbing MoS2 phase doped material, which is the same as in Embodiment 1, except that in step S2, the MoS2 nanosheets containing S vacancies are placed in a tube furnace and annealed at 200°C for 24 h, and then allowed to cool naturally to room temperature to obtain 1T@2H MoS2 phase doped material. All other process parameters are the same as in Embodiment 1.

[0043] Example 4 This embodiment provides a method for preparing a full-spectrum light-absorbing MoS2 phase-doped material, which is the same as in Embodiment 1, except that in step S2, the MoS2 nanosheets containing S vacancies are placed in a tube furnace and annealed at 260°C for 16 h, and then allowed to cool naturally to room temperature to obtain 1T@2H MoS2 phase-doped material. All other process parameters are the same as in Embodiment 1.

[0044] Example 5 This embodiment provides a method for preparing a full-spectrum light-absorbing MoS2 phase doped material, which is the same as in Embodiment 1, except that in step S2, the MoS2 nanosheets containing S vacancies are placed in a tube furnace and annealed at 260°C for 20 h, and then allowed to cool naturally to room temperature to obtain 1T@2H MoS2 phase doped material. All other process parameters are the same as in Embodiment 1.

[0045] Example 6 This embodiment provides a method for preparing a full-spectrum light-absorbing MoS2 phase-doped material, which is the same as in Embodiment 1, except that in step S2, MoS2 nanosheets containing S vacancies are placed in a tube furnace and annealed at 260°C for 48 h, and then allowed to cool naturally to room temperature to obtain 1T@2H MoS2 phase-doped material. All other process parameters are the same as in Embodiment 1.

[0046] Example 7 This embodiment provides a method for preparing light-absorbing MoS2 phase doped material, which is the same as in embodiment 1, except that in step S4, a cylinder is 3D printed using polylactic acid as the raw material as the substrate. The cylinder has a height of 3cm and a radius of 3cm. All other process parameters are the same as in embodiment 1.

[0047] Example 8 This embodiment provides a method for preparing light-absorbing MoS2 phase doped material, which is the same as in embodiment 1, except that in step S4, a cone is 3D printed using polylactic acid as raw material as a substrate. The cone has a height of 3cm and a base radius of 3cm. All other process parameters are the same as in embodiment 1.

[0048] Performance testing Figure 1This is a structural diagram of the full-spectrum light-absorbing MoS2 phase-doped material prepared in Example 1. The full-spectrum light-absorbing MoS2 phase-doped material in Example 1 constitutes a Janus structure, which includes an outer layer of MoS2-loaded hydrophobic spandex fabric (i.e., a photothermal layer), an intermediate layer of modified hydrophilic spandex fabric (i.e., an absorbent layer), and a bottom 3D-printed model serving as an insulating layer. Due to the asymmetric wettability of the Janus structure, the evaporation process mainly occurs at the interface between the hydrophilic and hydrophobic films, and salt precipitates below the interface, reducing the impact of salt crystallization on the photothermal layer.

[0049] Figure 2 The diagram shows photothermal evaporation devices of different shapes assembled from light-absorbing MoS2 phase doped materials prepared on substrates of different shapes in Examples 1 and 7-8.

[0050] Blue foam (polystyrene foam, which serves to insulate against heat) is placed above water, and a limiting hole is made on the foam. The full-spectrum light-absorbing MoS2 phase doped material prepared in Example 1 is embedded in the limiting hole. The modified hydrophilic spandex cloth in the middle layer guides the water to the photothermal layer (i.e., the hydrophobic spandex cloth loaded with MoS2) for photothermal performance testing.

[0051] Figure 3 The images show the water contact angle test results of the modified spandex fabric in Example 1 and the spandex fabric coated with polytetrafluoroethylene. Specifically, the hydrophilic modified spandex fabric used as the absorbent layer in step S3 of Example 1 exhibits excellent hydrophilicity with a water contact angle of 25.24°. The photothermal layer, due to the hydrophobicity of the MoS2 loading itself and the further application of PTFE curing agent during the coating process, exhibits even stronger hydrophobicity, with a water contact angle of 117.83°.

[0052] Figure 4 The graph shows a comparison of the photothermal evaporation performance of light-absorbing MoS2 phase doped materials prepared on substrates of different shapes in Examples 1 and 7-8. Figure 4 In this context, Cylinder corresponds to Example 7, Cone corresponds to Example 8, and Hemisphere corresponds to Example 1.

[0053] Figure 4 The evaporation performance of light-absorbing MoS2 phase-doped materials prepared on substrates of different shapes in Examples 1 and 7-8 for pure water; specifically, Figure 4 The formula for calculating the mass change of water, represented by the vertical axis, is: ; In the formula, m is the mass loss of water, m is the mass of pure water before evaporation, m2 is the mass of pure water after evaporation, and S is the evaporation area.

[0054] from Figure 4As can be seen from the data, the light-absorbing MoS2 phase doped material prepared on a cylindrical substrate in Example 7 has a mass loss of 0.605 kg m³ to pure water. -2 In Example 8, the light-absorbing MoS2 phase doped material prepared on a conical substrate experienced a mass loss of 0.610 kg m³ to pure water. -2 In Example 1, the light-absorbing MoS2 phase-doped material prepared on a hemispherical substrate experienced a mass loss of 0.612 kg m³ to pure water. -2 .

[0055] Furthermore, in Figure 4 Based on this, the evaporation rate (mass loss of water / time) of pure water for the light-absorbing MoS2 phase-doped materials prepared on substrates of different shapes in Examples 1 and 7-8 was calculated; the stable evaporation rate of the light-absorbing MoS2 phase-doped material prepared on a cylindrical substrate in Example 7 was calculated to be 1.21 kg m³. -2 h -1 In Example 8, the evaporation rate of the light-absorbing MoS2 phase-doped material prepared on a conical substrate was 1.22 kg m³. -2 h -1 The evaporation rate of the light-absorbing MoS2 phase-doped material prepared on a spherical substrate in Example 1 was 1.24 kg m³. -2 h -1 The light-absorbing MoS2 phase doped material prepared on a hemispherical substrate has the highest evaporation rate.

[0056] Further calculations of the photothermal conversion efficiency revealed that the photothermal conversion efficiency of the light-absorbing MoS2 phase-doped material prepared on a cylindrical substrate in Example 7 was 75.86%, the photothermal conversion efficiency of the light-absorbing MoS2 phase-doped material prepared on a conical substrate in Example 8 was 76.49%, and the photothermal conversion efficiency of the light-absorbing MoS2 phase-doped material prepared on a hemispherical substrate in Example 1 was 77.74%. This indicates that the hemispherical evaporator exhibits higher evaporation efficiency under the same illumination conditions due to its larger effective photothermal area.

[0057] The formula for calculating photothermal conversion efficiency is as follows: To stabilize the evaporation rate (unit: kg m³) -2 h -1 ) , S represents the change in water mass per unit time (unit: kg), and S represents the evaporation area (unit: m²).

[0058] To stabilize the evaporation rate (unit: kg m³) -2h -1 ) ; The phase transition enthalpy is given by using the value of water at its standard boiling point of 100°C (2257 kJ kg⁻¹). ; For sensible heat, It is a constant (4.18 J g) -1 K -1 ) , This refers to the temperature difference between the steam and the ambient temperature. To standardize solar radiation intensity, it is set to 1.0 kW m. -2 ; Optical concentration (value is 1).

[0059] Figure 5 The images show SEM images of the spandex fabric in Example 1 before and after loading with MoS2 phase doped material.

[0060] The surface of spandex fibers is smooth, but after loading MoS2, nanosheet-like materials are uniformly distributed on the fiber surface. Further magnified SEM images show that the layered nanosheet structure of MoS2 is relatively uniformly stacked on the surface of the photothermal layer, providing abundant interfaces for light absorption and heat conduction, thus enhancing the photothermal performance of the material.

[0061] Figure 6 The image shows the FTEM image of the 1T@2H MoS2 phase doped material prepared in step S2 of Example 1.

[0062] Two distinct lattice regions were observed on the same basal plane, with the 1T and 2H phases alternating, exhibiting a local phase transition. This alternating arrangement indicates that during heat treatment, different regions on the MoS2 basal plane underwent a local phase transition from the 2H phase to the 1T phase, forming a 1T@2H phase-doped structure. Further magnification clearly reveals the hexagonal crystal structure of the 2H phase MoS2 and the tetragonal crystal structure of the 1T phase MoS2. The difference in crystal structure between these two phases is particularly evident in high-resolution images, confirming the precise existence of the 1T@2H phase-doped array.

[0063] Figure 7 The images show the XRD patterns of 1T@2H MoS2 phase-doped materials prepared under different conditions in step S2 of Examples 1-3, as well as the original MoS2 nanosheets in step S1. Figure 7In this context, MoS2 (260℃ 24h) is the 1T@2H MoS2 phase doped material prepared in Example 1, MoS2 (260℃ 12h) is the 1T@2H MoS2 phase doped material prepared in Example 2, MoS2 (200℃ 24h) is the 1T@2H MoS2 phase doped material prepared in Example 3, and MoS2 represents the S-vacant MoS2 nanosheets prepared in Example 1.

[0064] from Figure 7 As can be seen from the data, compared with the standard diffraction data of MoS2 (PDF#037-1492), the diffraction peak positions of all samples are consistent with the standard peak positions, indicating that the prepared MoS2 has high purity, that is, no impurities were introduced by heat treatment. Further magnification of the diffraction region near the (002) crystal plane reveals slight shifts in the diffraction peak positions of the samples under different heat treatment conditions. Compared with the standard diffraction peak of 14.38°, the diffraction peaks of the MoS2 (260℃-24h), MoS2 (260℃-16h), and MoS2 (200℃-24h) samples shifted to the right by 0.2°, 0.18°, and 0.16°, respectively. Since the lattice parameter of the 1T phase MoS2 is slightly larger than that of the 2H phase MoS2, the peak shift to some extent proves that the local lattice structure of the samples has changed. The diffraction peak shift of the MoS2 (260℃-24h) sample is the most significant, indirectly indicating that the local phase change from the 2H phase to the 1T phase is more pronounced under this condition.

[0065] Figure 8 The image shows the XPS pattern of the 1T@2H MoS2 phase doped material prepared in step S2 of Example 1.

[0066] In the Mo 3d spectrum ( Figure 8 In (a), two distinct peaks were observed at 229.78 eV and 231.98 eV, respectively, which correspond to Mo 3d. 5 / 2 and Mo 3d 3 / 2 The orbitals are consistent with the electronic structure of the 2H phase MoS2. Further peak decomposition analysis showed that the spectrum could be separated into two groups of characteristic peaks belonging to the 1T and 2H phases of MoS2, respectively. Among them, the peaks at 229.88 eV and 232.08 eV belong to the 2H phase Mo(IV)3d orbitals. 5 / 2 and 3D 3 / 2 The peaks at 229.28 eV and 232.28 eV correspond to the 1T phase Mo(IV)3d 5 / 2 and 3D 3 / 2 In addition, an S 2s peak was detected at 227.08 eV, which originated from sulfur atoms in the Mo-S bond.

[0067] Figure 8b) shows the S 2p spectrum, where the doublets at 162.46 eV and 163.63 eV are attributed to the S 2p of the 2H phase MoS2. 3 / 2 and S 2p 1 / 2 The peaks at 162.09 eV and 163.32 eV correspond to the S 2p orbitals of the 1T phase MoS2, while the peaks at 162.09 eV and 163.32 eV correspond to the S 2p orbitals of the 1T phase MoS2. 3 / 2 and S 2p 1 / 2 This further proves the coexistence of the 1T phase and the 2H phase in the MoS2 sample.

[0068] Figure 9 The images show the UV-Vis-NIR spectra of 1T@2H MoS2 phase doped materials prepared under different conditions in steps S2 of Examples 1, 2, 4-6. Figure 9 In this context, MoS2 (260℃ 24h) is the 1T@2H MoS2 phase doped material prepared in Example 1, MoS2 (260℃ 12h) is the 1T@2H MoS2 phase doped material prepared in Example 2, MoS2 (260℃ 16h) is the 1T@2H MoS2 phase doped material prepared in Example 4, MoS2 (260℃ 20h) is the 1T@2H MoS2 phase doped material prepared in Example 5, and MoS2 (260℃ 48h) is the 1T@2H MoS2 phase doped material prepared in Example 6. MoS2 represents the S-vacancy MoS2 nanosheets prepared in Example 1.

[0069] Compared to untreated MoS2, the heat-treated sample exhibited enhanced absorption across the entire spectral range, particularly showing a significant increase in absorption in the near-infrared region above 800 nm. The absorption intensity further increased with increasing heat treatment time, reaching a peak at 24 h. However, after 24 h of heat treatment, the absorption capacity ceased to increase and instead showed a decreasing trend.

[0070] Figure 10 , 11 The desalination performance of the full-spectrum light-absorbing MoS2 phase-doped materials prepared under different conditions in Examples 1-3 is demonstrated. The different materials exhibit desalination performance under one solar intensity (approximately 1000 W / m²). -2 The graph below shows the mass loss curve, water evaporation rate, and photothermal conversion efficiency of Bohai Sea water (where Pure water represents the Bohai Sea water evaporating naturally for 1 hour without the use of photothermal materials; the calculation of the mass loss curve, water evaporation rate, and photothermal conversion efficiency is the same as above). Figure 4 ); Figure 10 , 11In this context, MoS2(260℃-24h) refers to the full-spectrum light-absorbing MoS2 phase-doped material finally prepared in Example 1, MoS2(260℃-12h) refers to the full-spectrum light-absorbing MoS2 phase-doped material prepared in Example 2, MoS2(200℃-24h) refers to the full-spectrum light-absorbing MoS2 phase-doped material prepared in Example 3, Pure water refers to the initial Bohai Sea water used, and MoS2 refers to the S-vacancy MoS2 nanosheets prepared in Example 1.

[0071] Figure 10 The change in the mass loss of Bohai Sea water over time during the evaporation experiment of the full-spectrum light-absorbing MoS2 phase doped materials in Examples 1-3; Figure 11 The evaporation rate and photothermal conversion efficiency of the full-spectrum light-absorbing MoS2 phase doped materials in Examples 1-3 were calculated after an evaporation experiment lasted 1 h. from Figure 10 , 11 As can be seen, the MoS2 (260℃-24h) sample experienced the greatest mass loss, a result consistent with the UV-Vis-NIR spectral analysis. The evaporation rate and photothermal conversion efficiency of each sample were calculated. After loading with MoS2, the evaporation rate increased significantly, reaching more than six times that of the unloaded material. In particular, the heat-treated MoS2 (200℃-24h), MoS2 (260℃-24h), and MoS2 (260℃-12h) samples exhibited even higher evaporation rates, reaching 1.067 kg·m³. -2 ·h -1 1.222 kg·m -2 ·h -1 and 1.270 kg·m -2 ·h -1 The corresponding photothermal conversion efficiencies were 76.69%, 87.07%, and 90.52%, respectively. This improvement is mainly attributed to the LSPR effect of 1T@2H MoS2 in the photothermal conversion process. Due to the enhanced intrinsic lattice vibration and electron migration capabilities of 1T@2H MoS2, radiative energy can be converted into thermal energy more rapidly.

[0072] Figure 12 The graph shows the changes in various ions of the full-spectrum light-absorbing MoS2 phase doped material prepared in Example 1 before and after evaporation from Bohai Sea water. Figure 12 In the text, "Before desalination" represents the concentration of each ion in the Bohai Sea before evaporation, and "After desalination" represents the concentration of each ion in the Bohai Sea after evaporation.

[0073] Na in sea water + K + Ca2+ and Mg 2+ The initial ion concentrations were 11500 mg·L⁻¹. -1 860 mg·L -1 585 mg·L -1 and 496 mg·L -1 After photothermal evaporation, the concentrations of these ions decreased significantly, dropping to 8.5 mg·L⁻¹. -1 2.3 mg·L -1 4.2 mg·L -1 and 0.8 mg·L -1 All of these are far below the World Health Organization (WHO) drinking water standards.

[0074] Figure 13 The evaporation rate of the full-spectrum light-absorbing MoS2 phase doped material prepared in Example 1 during the evaporation of Bohai Sea water was measured over 10 desalination cycles.

[0075] The full-spectrum light-absorbing MoS2 phase-doped material maintained a very stable evaporation rate after 10 cycles, with a rate of 1.26 kg·m⁻² after 10 cycles. -2 ·h -1 .

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a full-spectrum light-absorbing MoS2 phase-doped material, characterized in that, Includes the following steps: MoS2 nanosheets containing S vacancies were obtained by electrolytic expansion and ultrasonic exfoliation of molybdenite sheets. Annealing of MoS2 nanosheets containing S vacancies yields 1T@2H MoS2 phase-doped materials with full-spectrum absorption. Spandex fabric is prepared by immersing it in water-based polyurethane to obtain a hydrophilic modified spandex fabric. A substrate is bonded to a modified spandex fabric, and then a spandex fabric is bonded to the surface of the modified spandex fabric. After mixing 1T@2H MoS2 phase doped material with ethanol, the mixture was coated onto the surface of spandex cloth, dried, and then coated with polytetrafluoroethylene emulsion and dried to obtain a full-spectrum absorbance MoS2 phase doped material. MoS2 nanosheets containing S vacancies were obtained by electrolytic expansion and ultrasonic exfoliation of molybdenite sheets, specifically including the following steps: Using molybdenite sheets as cathodes, electrolysis is performed by placing the cathode and anode in an electrolyte and connecting them to a power source to obtain expanded molybdenite sheets. Expanded molybdenite sheets were used as anodes for continuous electrolysis to obtain molybdenite sheets containing S vacancies. Molybdenite flakes containing S vacancies were immersed in NMP and ground to obtain a pre-exfoliated product. The pre-exfoliated product was sonicated, centrifuged, filtered, and freeze-dried to obtain MoS2 nanosheets containing S vacancies. The electrolysis control process parameters are as follows: the electrolyte is a 0.5~0.8 mol / L NaOH solution, and the current density is 0.02~0.03 A / cm². 2 The electrolysis time is 10~12 hours; In the step of annealing MoS2 nanosheets containing S vacancies, the annealing temperature is 200~360℃ and the time is 12~24h.

2. The method for preparing the full-spectrum light-absorbing MoS2 phase-doped material as described in claim 1, characterized in that, In the step of sonicating, centrifuging, filtering, and freeze-drying the pre-exfoliated product to obtain MoS2 nanosheets containing S vacancies, the ultrasonic power is 400~500W, the ultrasonic time is 4~6 h, the centrifugation rate is ~6000 rpm, and the centrifugation time is 20~30 min.

3. The method for preparing the full-spectrum light-absorbing MoS2 phase-doped material as described in claim 1, characterized in that, In the step of immersing the spandex in water-based polyurethane, the immersion time is 0.5~1h.

4. The method for preparing the full-spectrum light-absorbing MoS2 phase-doped material as described in claim 1, characterized in that, In the step of mixing 1T@2HMoS2 phase doped material and ethanol, the mass-to-volume ratio of 1T@2HMoS2 phase doped material and ethanol is (20~40) mg:(6~10) mL.

5. The method for preparing the full-spectrum light-absorbing MoS2 phase-doped material as described in claim 1, characterized in that, The substrate is a polylactic acid substrate, and the substrate is a hemispherical substrate.

6. A full-spectrum light-absorbing MoS2 phase-doped material, characterized in that, It is prepared by any one of the preparation methods described in claims 1 to 5.

7. A full-spectrum light-absorbing MoS2 phase doped material prepared by any one of the preparation methods described in claims 1 to 5, or the full-spectrum light-absorbing MoS2 phase doped material described in claim 6, is used as a solar-driven interfacial evaporation material for seawater desalination or high-salinity wastewater treatment.

Citation Information

Patent Citations

  • Solar water evaporation photothermal conversion material and preparation method and application thereof

    CN117487527A

  • Manufacturing method of wide-spectrum collaborative complementary thin film solar cell

    CN119698100A